Edward Snowden disclosures turn the fears of surveillance into reality: the impact and transformation in information security - Mohamed Mahmoud, Fatimetou Zahra; Zeki, Akram M. (Little Lion Scientific Islamabad Pakistan, 2016)
More than two years passed since the biggest event on information security and privacy which is the disclosure of very sensitive documents on the National Security Agency in United States. Those disclosures had a lot of resonance and impact in term of discussions between people who supported the act and others who consider it as crime and breach of trust. The fact, is that the impact was huge not only regarding information technology but it has been extended to economy and politics. This paper provide a holistic view and analyse of the current situation of information technology security and privacy especially with the lack and limited researches that have been done to study the transformation in information security strategies, policies and law after Edward Snowden disclosures and how those transformation had affect the technology, business and politics in various countries. This paper describes in detail and explain how the disclosures done by Edward Snowden has happen, What is the most dangerous programs used by NSA to violate people privacy, The reaction of different countries such as USA and Canada toward this revelations and the change and transformation in policies, strategies and law regarding information security and privacy. Furthermore, how this revelations gave affect the relationship and make it more complicated between China and USA. In addition, many countries focus in developing law to protect their citizens’ privacy and security from any foreign surveillance. Moreover, how this revelations has been a lessons to NSA to strengthen its inside protection, lessons to companies to not trust to any internet company to store their business data and how to improve their security systems.